Synthesis, characterization and evaluation of in vitro toxicity in hepatocytes of linear polyesters with varied aromatic and aliphatic co-monomers - Kakde, Deepak; Powell, Leagh G.; Bansal, Kuldeep K.; Howdle, Steve; Irvine, Derek; Mantovani, Giuseppe; Millar, Gavin; Dailey, Lea Ann; Stone, Vicki; Johnston, Helinor J.; Alexander, Cameron (Elsevier, 2016)
Polyesters are extensively used in drug delivery because of their controllable biodegradation properties and perceived favorable cytocompatibility. However, new ester-based materials are continually being sought which can be produced from readily accessible monomers, which can be tuned for drug encapsulation and which retain good cellular compatibilities. In this study, 5 polyesters of similar molar mass were synthesized by reacting 1,10-decanediol with different ratios of succinic acid/phenylsuccinic acid and the effect of the phenyl side-chain group addition on polymer properties relevant to drug delivery was investigated. A polymer with a 70/30 ratio of succinic acid and phenylsuccinic acid was selected based on its ability to encapsulate a model dye in nanoparticle (NP) formulations, and was found to be slowly degradable in phosphate buffered saline (PBS) but more rapidly degraded in the presence of a lipase. The compatibility of NP formulations of this polymer either with or without a Pluronic F68 stabilizing coating was assessed in vitro using the C3A hepatocyte cell line. Cell viability was assessed, at NP concentrations ranging from 4.68–300 μg mL− 1 24 h post-exposure, using the Alamar Blue, CDFA and Neutral Red assays. C3A cells internalized both coated and uncoated polyester NPs to a similar extent, with uptake observed to increase over time (10–1440 min). Although cell viability was > 80% at the concentrations tested, in all assays, it was found that a Pluronic F68 coated poly (decanediol-phenylsuccinate-co-succinate) stimulated significant DNA damage driven by an oxidant mechanism, whereas the non-coated polyester analogue and the Pluronic F68 alone had no effect. The results obtained suggest that new polyesters can be synthesized with desirable properties from the materials perspective but formulation with additional excipients requires careful evaluation for drug delivery applications.